2015
DOI: 10.1037/spq0000099
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-randomized trial demonstrating impact on academic achievement of elementary social-emotional learning.

Abstract: This study evaluated the results of a social and emotional learning (SEL) program on academic achievement among students attending a large, urban, high-risk school district. Using a cluster-randomized design, 24 elementary schools were assigned to receive either the intervention curriculum (Promoting Alternative Thinking Strategies, or PATHS) or a curriculum that delivered few if any SEL topics (i.e., the control group). In addition to state mastery test scores, demographic data, school attendance, and dosage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
4
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 26 publications
6
60
4
7
Order By: Relevance
“…A efetividade do THS na promoção de habilidades relacionadas a competência acadêmica e aprendizado, como habilidades de leitura, escrita e aritmética, também foi observada em outros estudos com populações em situação de vulnerabilidade (Lopes, Del Prette, & Del Prette, 2013;Noltemeyer & Bush, 2013;Schonfeld et al, 2015). Em estudo envolvendo 24 escolas localizadas em áreas de vulnerabilidade, foi observado que os estudantes envolvidos apresentaram aumento significativo nos níveis de aritmética, leitura e escrita (Schonfeld et al, 2015). Esses resultados explicitam que o THS pode atuar na prevenção e redução do fracasso escolar e seus impactos na vida futura dos estudantes (Lopes et al, 2013;Noltemeyer & Bush, 2013).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A efetividade do THS na promoção de habilidades relacionadas a competência acadêmica e aprendizado, como habilidades de leitura, escrita e aritmética, também foi observada em outros estudos com populações em situação de vulnerabilidade (Lopes, Del Prette, & Del Prette, 2013;Noltemeyer & Bush, 2013;Schonfeld et al, 2015). Em estudo envolvendo 24 escolas localizadas em áreas de vulnerabilidade, foi observado que os estudantes envolvidos apresentaram aumento significativo nos níveis de aritmética, leitura e escrita (Schonfeld et al, 2015). Esses resultados explicitam que o THS pode atuar na prevenção e redução do fracasso escolar e seus impactos na vida futura dos estudantes (Lopes et al, 2013;Noltemeyer & Bush, 2013).…”
Section: Discussionunclassified
“…As mudanças vivenciadas pelos estudantes estão associadas a novas demandas de relacionamentos interpessoais que podem requerer deles o domínio de habilidades sociais, como: pedir ajuda, resolver conflitos, falar em público, adaptar-se ao ambiente e aos novos métodos acadêmicos. Quando há déficit quanto as habilidades necessárias para lidar com as demandas dessa nova fase, pode haver o desencadeamento de estresse, fracasso escolar, transtornos psíquicos, problemas comportamentais internalizantes e externalizantes (Schonfeld et al, 2015;Trach, Lee & Hymel, 2017).…”
Section: Resumen -Efectos De Un Entrenamiento De Habilidades Socialesunclassified
“…Schonfeld et al, 2015;Rimm-Kaufmann et al, 2014) following this direction and focusing more specifically on the relationship between SEL and academic achievement. The studies that followed (Schonfeld et al, 2015;Rimm-Kaufmann et al, 2014) confirmed that SEL enhances students' connection to school, classroom behaviour and academic achievement also when controlling for cognitive abilities (Teo, Carlson, Mathieu, Regeland, & Sroufe, 1996, in Malecki & Elliot, 2002 which is all related to ESL prevention. similarly compared the efficacy of various school SEL prevention programmes in a meta-analysis of 165 studies (ranging from individual counselling to behaviour modification programmes).…”
Section: Sel In School and Its Role In Eslmentioning
confidence: 99%
“…Numerous randomised controlled trials (RCTs) have consistently established small-to-moderate effects on a range of outcomes, including children's social and emotional skills, externalising problems (e.g. aggressive behaviour) and academic attainment [15][16][17][18][19][20][21][22][23][24][25]. However, many trials finding positive effects of PATHS have involved or been led by the developer.…”
Section: Introductionmentioning
confidence: 99%